SLM-printed EUROFER steel for fusion applications - Ramil Gaisin; Carsten Bonnekoh; Simon Bonk; Heiko Neuberger; Vladimir Chakin; Michael Rieth (Nuclear Materials and Energy)
This study investigates selective laser melting (SLM) of atomized EUROFER97 powder for fusion applications, focusing on two fabrications and their resulting microstructure, tensile properties, impact toughness, and leak-tightness. Optimized powder preparation improved chemical composition and grain size after heat treatment, enhancing Charpy impact toughness with an upper shelf energy surpassing the EUROFER97 standard and a lower ductile-to-brittle transition temperature (−120 °C vs. −100 °C). Tensile properties, including yield and ultimate strength and elongation, were similar to the EUROFER97 reference material.SLM-printed capsules demonstrated excellent leak-tightness, with helium leak rates well below ITER requirements, and burst tests confirmed ultimate strengths exceeding 700 MPa. These findings showcase potential of SLM for creating complex components for fusion reactor blankets with tailored mechanical properties.